031 Provision of an education and training programme by the CATS team. (December 2018) - Roberts, C
Abstract : Introduction: The Children's Acute Transport Service (CATS) is a stand-alone paediatric critical care transport service for the North Thames region performing approximately 1200 intensive care transfers a year. There are 32 district general hospitals (DGH's) in this region; to foster a collaborative approach and maintain good relationships, each hospital is supported by a CATS consultant and core nurse. To ensure the continued provision of high-quality care for critically ill children the link consultant and nurse provide outreach training and education to all hospitals in our region; in 2016–2017 we provided outreach for approximately 1200 people. Method: The format of outreach days varies depending on local preference but generally consists of presentations of referral and transport activity, case-based discussions, challenging cases, and simulation. We encourage multi-disciplinary attendance. In addition to outreach, we provide lectures for the HDU, PICU, and ANP modules, study days held by DGH's, and we contribute to the intensive care modular training programme at Great Ormond Street Hospital. We also run two external courses one is a full day of immersive sim attended by anaesthetists, paediatricians, nurses and ODP's, and the other, also a multi-disciplinary study day that is a combination of interactive lectures and workshops. Results: All education and outreach evaluates well with comments such as 'Really helpful day' 'Interesting understanding of what CATS do, interesting to practice and discuss' 'Please come back and do some more sim with us'. Conclusion: DGH's request more frequent sessions and we are exploring alternatives such as teleconferencing which is currently mostly used for 'hot' debriefs. We are keen to use social media to increase our presence within the region and to provide short training videos that teams could access easily.